Mutation of the gene promoter synthase nitric oxide eNOS T786С in patients with pseudarthrosis of long bones: relationship with lipid levels and endothelial function - Bezsmertnyi Yu.O. (Medičnì Perspektivi)
Objective: The prevalence of gene promoter polymorphism eNOS T786С and its relationship with the level of lipids and vascular endothelial function in patients with pseudoarthrosis of long bones was investigated. Materials and methods. In 118 patients with pseudoarthrosis of long bones frequency of mutation of gene promoter eNOS T786C was studied and its relationship to lipid levels and vascular endothelial function was determined. The control group consisted of 48 patients with consolidated diaphyseal fractures, representative by age, gender and location of the damage. Results and discussion. Pathological homozygotes eNOS 786-CC accumulate predominantly in patients with hypoplastic and atrophic type of pseudoarthrosis. The frequency of genotypes distribution in patients with normoplastic type of pseudoarthrosis corresponded to the same in people with consolidated fractures. In patients with genotype eNOS 786-CC more often individuals with aberrant lipid levels and structural and functional changes in the common carotid, brachial and femoral arteries are identified. Conclusions. In patients with pseudarthrosis of long bones tendency to decrease in the proportion of normal homozygotes (786-CT), increase in heterozygotes (786-CT) and the proportion of individuals with abnormal genotype 786-CC is observed. The mutation in gene T786C eNOS was associated with the development of hypoplastic and aplastic types of pseudarthrosis, increasing the proportion of persons with aberrant lipid levels, endothelial dysfunction of the central and peripheral vessels.